The Long-Term Human Capital and Health Impacts of a Pollution Reduction Programme - Nanna Fukushima; Stephanie von Hinke; Emil N. Sørensen (Institute of Labor Economics (IZA), 2024)
This paper investigates the effects of the staggered roll-out of a pollution reduction programme introduced in the UK in the 1950s. The policy allowed local authorities to introduce so-called "Smoke Control Areas" (SCAs) which banned smoke emissions. We start by digitizing historical pollution data to show that the policy led to an immediate reduction in black smoke concentrations. We then merge data on the exact location, boundary and month of introduction of SCAs to individual-level outcomes in older age using individuals' year-month and location of birth. We show that exposure to the programme increased individuals' birth weights as well as height in adulthood. We find no impact on their years of education or fluid intelligence.
Keywords: I18; I15; C21; C22; 330; control areas; developmental origins; staggered treatment effects